Kedudukan dan Fungsi Penjabat Bupati dalam Penyelenggaraan Pemerintahan Daerah di Kabupaten Lembata (Studi Terhadap Penjabat Bupati Lembata Tahun 2022-2023 dan 2023-2024) - Katarina Peni Lajar; Kotan Y. Stefanus; Yohanes G. Tuba Helan (Konsensus : Jurnal Ilmu Pertahanan, Hukum dan Ilmu Komunikasi, 2024)
This research is a normative judicial research supported by a conceptual juridical approach and a statutory approach using primary legal materials and secondary legal materials collected through interviews, observations and literature studies and processed using editing and classification techniques and analyzed in a qualitative descriptive manner. The results of the study show that the Position and Function of the Acting Regent in the Implementation of Regional Government in Lembata Regency has not run optimally, not all Regional Officials have good ability in organizing government affairs and community interests both in the village and at the sub-district level, as well as carrying out balanced development between physical development and non-physical development.